Metabolic Bulk Volume is an independent prognostic factor and facilitates identifying high risk cases for DLBCL patients treated with the R-CHOP - Cui, Silu; Luan, Panpan; Hu, Yuxiao; Jiang, Qi (Frontiers in Oncology, 2026)
ObjectiveThe purpose of this study was to evaluate the prognostic value of metabolic bulk volume (MBV), a baseline 18-fluorode-oxyglucose positron emission computed tomography (18F-FDG PET/CT) derived indicator characterizing bulky disease, in DLBCL patients treated with R-CHOP.Methods311 consecutive newly diagnosed Diffuse Large B-Cell Lymphoma (DLBCL) patients were retrospectively evaluated. Estimating MBV, Distance between the centers of the two farthest lesions (Dmax) and Total metabolic tumour volume (TMTV) as semiquantitative metabolic parameters. Receiver Operating Characteristic (ROC) curve analysis was used to determine the optimal cut-off values. Progression-Free Survival (PFS) and Overall Survival (OS) were the endpoints for evaluating prognosis. PFS and OS were estimated using Kaplan-Meier curves, and comparisons were performed via log-rank test.ResultsMultivariate analysis showed that only two baseline 18F-FDG PET factors, MBV and Dmax, remained significant for OS (P = 0.004 and P < 0.0001). Combining high MBV and high Dmax generated three risk groups for PFS (P < 0.0001) and OS (P < 0.0001). This was equally effective as the three-risk-group stratification by high TMTV combined with high Dmax for both PFS (P < 0.0001) and OS (P < 0.0001). Further stratification of the three risk groups generated by the combination of high TMTV and high Dmax using MBV showed that MBV could further stratify PFS in both the low-risk group (P < 0.0001) and high-risk group (P = 0.015), as well as OS in high-risk group (P = 0.001).ConclusionMBV was an independent prognostic factor for DLBCL patients. The combination of MBV with parameters reflecting tumor dissemination distribution or total tumor burden further improved the risk stratification for staging in DLBCL patients.